2002
DOI: 10.1021/bi0268899
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Structural Changes in Carboxyl-Terminal Peptides of Transducin α-Subunit upon Binding a Soluble Mimic of Light-Activated Rhodopsin

Abstract: Although a high-resolution crystal structure for the ground state of rhodopsin is now available, portions of the cytoplasmic surface are not well resolved, and the structural basis for the interaction of the cytoplasmic loops with the retinal G-protein transducin (G(t)) is still unknown. Previous efforts aimed at the design, construction, and functional characterization of soluble mimics for the light-activated state of rhodopsin have shown that grafting defined segments from the cytoplasmic region of bovine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Specifically, HPTRX/CDEF displayed virtually identical kinetics of G t activation when compared with light-activated ROS rhodopsin (38), suggesting that the CD and EF loops in the fusion protein can adopt a conformation that is a close approximation to that present in R*. It was also shown that HPTRX/CDEF bound G t␣ (340 -350) peptides (52) inducing structural changes in these peptides analogous to those observed previously in studies with native, light-activated rhodopsin in ROS membranes (28 -30).…”
Section: Biochemical Analysis Of a Complex Between A Solublementioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, HPTRX/CDEF displayed virtually identical kinetics of G t activation when compared with light-activated ROS rhodopsin (38), suggesting that the CD and EF loops in the fusion protein can adopt a conformation that is a close approximation to that present in R*. It was also shown that HPTRX/CDEF bound G t␣ (340 -350) peptides (52) inducing structural changes in these peptides analogous to those observed previously in studies with native, light-activated rhodopsin in ROS membranes (28 -30).…”
Section: Biochemical Analysis Of a Complex Between A Solublementioning
confidence: 95%
“…Biochemical and structural studies (38,52) have shown that some of these rhodopsin cytoplasmic fragment/thioredoxin fusion proteins exhibit properties similar to those of R*. In particular, the HPTRX/ CDEF fusion protein, which contains tandemly linked segments from the CD (amino acids 132-154) and EF (amino acids 231-252) loops of rhodopsin (Fig.…”
Section: Biochemical Analysis Of a Complex Between A Solublementioning
confidence: 99%
“…The hypothesis was that TM6 movement exposes a binding site for the transducin Gα subunit (GTα) C-terminal tail (GTα C-term). The GTα C-term was known to be required for rhodopsin-transducin interaction [119], and peptide analogues of this region bind rhodopsin with high affinity [120] and become structured in the process [121, 122]. …”
Section: From Molecular To Cellular Insight In Visual Rhodopsin Fumentioning
confidence: 99%
“…Several lines of evidence show that the rhodopsin cytoplasmic face directly interacts with the G T␣ C terminus. For example, peptides and peptide analogues corresponding to the G T␣ C terminus can bind and stabilize MII rhodopsin (18 -20), and binding induces structure in these peptides (21)(22)(23)(24). Rhodopsin mutagenesis studies show that residues in intracellular loops i2 and i3 are important in this interaction (25)(26)(27)(28), and a photocross-linking probe on loop i3 at residue 240 on rhodopsin cross-links to this region of G T␣ (29).…”
mentioning
confidence: 99%